Spatiotemporal Distribution of Mesoporous Silica Nanoparticles in Tissue-Mimicking Collagen Using Lab-on-a-Chip Technology for Drug Carrier Diffusivity Evaluation - Hwang, Hae Won; Kim, Seongchan; Hwang, Hyerim; Han, Hyung-Seop; Jeon, Hojeong; Kim, Yu-Chan; Lee, Hyojin; Sun, Jeong-Yun; Ok, Myoung-Ryul (American Chemical Society, 2022)
As injected drugs finally diffuse to the target cells, a quantitative understanding of the diffusion behavior of drug molecules or drug carriers is essential for the determination of their efficacy or optimal doses. Here, we propose a method for determining the diffusivity (D, diffusion coefficient) of drug carriers in tissue-mimicking collagen in the lab-on-a-chip (LOC) platform and predict their spatiotemporal distribution using the calculated D. By controlling the concentrations of fluorescent mesoporous silica nanoparticles (MSNs) in each channel, the diffusion of fluorescent MSNs was induced and fluorescence gradients in collagen were produced and captured as images. The D of the MSNs by size was obtained by fitting the fluorescence profiles to the solution of Fick's second law. The D of MSNs varied by size from 2.98 x 10-10 m2/s (MSNs of 10 nm) to 1.14 x 10-11 m2/s (MSNs of 1 mu m). The spatiotemporal profiles of MSNs were calculated using the obtained D, and it was demonstrated that the concentration of MSNs with a size > 200 nm at 100 mu m from the gel-liquid interface will remain < 50% of that in the vessel-mimicking channel even after 3 h. As the analysis and prediction procedures based on fluorescence profile image processing and a least-squares fit to the solution are relatively simple, our results can be extended to various studies to narrow the gap between in vitro tests and animal experiments in drug or particle transport research through the calculation of the diffusion coefficient of drug candidates before animal experiments and might replace some parts of animal experiments of drug delivery studies.